Homoousios or Homoiosis: Redefining the Christian Image in the Wake of the Iconoclastic Controversy - Conty, Arianne (Religion and the arts, 2023)
This article will elucidate the philosophy of the image that developed in the wake of the Iconoclastic Controversy in the Eastern Christian Empire in the ninth Century. Iconophilia was finally reinstated after a wave of iconoclasm swept across the Empire. The controversy coincides with dramatic changes within the Byzantine empire, making it difficult to establish consensus amongst scholars regarding its possible causes. After discussing several of the theories that seek to explain the adoption of iconoclasm in the Byzantine Empire, we will seek to show how image veneration was transformed and differentiated from relic worship thanks to its encounter with iconoclasm. After reviewing icon veneration prior to the Iconoclastic Controversy, this article will elucidate the philosophy of the image developed by Patriarch Nicephorus in order to show how he differentiated veneration from idolatry by redefining the image as “similar to” (homoiosis) rather than consubstantial with (homoousios) its model. By differentiating image veneration from the theory of consubstantiality that was normative within Judaism and Islam, Christian philosophy of the image will differentiate resemblance from identity, inscription from circumscription, and thereby reveal iconoclasm to be in the eye of the beholder.